The effect of phytohormones and light on the germination of apple pollen with reduced viability - A. V. Pavlov; V. G. Verzhuk; D. D. Bondaruk (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the effect of phytohormones and light on the germination of apple pollen with reduced viability on an artificial nutrient medium is of importance, because it may facilitate an increase in the germination percentage among plant samples promising for breeding after their long-term preservation under low temperatures.Materials and methods. Pollen viability of the apple-tree cultivar ‘Krasnolistnaya’ was measured by germinating it on an artificial nutrient medium containing 10% sucrose solution and 0.8% agar. Drops of a distilled water suspension of pollen with added phytohormones were applied to the surface of the nutrient medium. Pollen was germinated in the dark (24 hours in a thermostat at 21°C) and under light (in an artificial light chamber at 21°C with a photoperiod of 16 hours of light / 8 hours of darkness). Results. Pollen of cv. ‘Krasnolistnaya’ with reduced viability most effectively germinated with the use of gibberellin at a concentration of 1 mg/l and 10 mg/l: the germination percentage was 22.3±0.8% and 21.8±1.3% respectively (сf. 10.9±1.5% in the reference). The most effective combination of phytohormones was gibberellin 10 mg/l + kinetin 10 mg/l – the percentage of germination was 22.8±6.3%; kinetin 1 mg/l + indolylbutyric acid 1 mg/l – the percentage of germination was 17.5±5.9% vs. 10.9±1.5% in the reference.Conclusion. Phytohormones were observed to have a significant effect on the germination of apple pollen with reduced viability. Effective concentrations and combinations of phytohormones that promote the germination of pollen with reduced viability have been identified. Light does not affect the germination of pollen with reduced viability.